2015
DOI: 10.1007/s12035-015-9304-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Ameliorates Early Brain Injury Following Subarachnoid Hemorrhage in Rats

Abstract: Background: Hydrogen sulfide (H 2 S) has shown a neuroprotective role in several cerebrovascular diseases. This study aimed to explore the underlying mechanisms of H 2 S in early brain injury after subarachnoid hemorrhage (SAH). Methods: One hundred seventy-seven male Sprague-Dawley rats were employed in this study. Sodium hydrosulfide (NaHS), a donor of H 2 S, was injected intraperitoneally at 60 min after SAH was induced by endovascular perforation. Western blot analysis determined the expression of several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 41 publications
3
50
0
1
Order By: Relevance
“…As the newest gasotransmitter, H 2 S is traditionally considered a poisonous gas and environmental pollutant. Evidence accumulated over the last decade reveals the potential value of H 2 S in the treatment of CNS diseases, including stroke and neurodegenerative diseases (Kida and Ichinose, 2015; Cui et al, 2016). Exogenous H 2 S donors confer neuroprotection in ischemic stroke, at least in part, owing to their anti-inflammatory properties (Yin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As the newest gasotransmitter, H 2 S is traditionally considered a poisonous gas and environmental pollutant. Evidence accumulated over the last decade reveals the potential value of H 2 S in the treatment of CNS diseases, including stroke and neurodegenerative diseases (Kida and Ichinose, 2015; Cui et al, 2016). Exogenous H 2 S donors confer neuroprotection in ischemic stroke, at least in part, owing to their anti-inflammatory properties (Yin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These pathophysiological processes could further induce global ischemic injury. Oxidative stress has been observed to play a critical role in EBI [26]. A recent in vitro experiment demonstrated that the upregulated protein expression of SIRT3 in PC12 cells secondary to oxygen-glucose deprivation (OGD) was an endogenous feedback response for neuroprotection [27].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its antioxidation function, SIRT3 is considered the potential therapeutic target for EBI [26]. Although the molecular mechanisms of SIRT3 function remain inadequate and controversial, its neuroprotective role was the primary focus of discussion in recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological examinations of scoring system (Table 1) were blindly performed at 48 h after SAH according to previous research (Cui et al, 2015), monitoring three aspects: appetite, activity, and neurological deficits. Neurological deficits of the experimental animals were scored as follows: (i) “no neurologic deficit” scored as 0; (ii) “potential or minimum neurologic deficit” scored as 1; (iii) “mild neurologic deficits” scored as 2 or 3; (iv) “severe neurologic deficit” scored as 4–6.…”
Section: Methodsmentioning
confidence: 99%